Introduction to polymer science and chemistry : a problem-solving approach - Chanda, Manas, 1940- (CRC Press, 2013)
"Preface A question asked during discussion, or even ahead of it, excites a student's mind and rouses his eagerness to probe, thus making the process of learning more thorough. During my teaching of polymer science and chemistry over a period of nearly four decades, I have thus always felt and believed that learning becomes much easier and deeper if problem solving with a question and answer approach is intimately integrated with the text. It was this belief and conviction that motivated me to embark on writing this new text on polymer science and polymer chemistry, even though I was fully aware that the field was already crowded with more than a dozen wellwritten polymer texts. Adopting a distinctly different and innovative approach, the text in this new polymer book has been laced with questions and answers at every step of the development of a theory or concept in each chapter. The book thus features a significantly large number (286) of solved problems interspersed with the text that is spread over 720 pages. In addition, a large number (277) of problems are included as end-of-chapter exercises and these are fully worked out in a separate Solutions Manual. As my experience in teaching has taught me the great value of dealing with numbers to deepen one's understanding, most of the problems with which the text is studded are chosen to be of numerical type. The same is true for exercise problems appended at the end of each chapter and each such problem is provided with numerical answers so that the reader can compare with his own"--Resumé vydavatele